THE RELATIONS BETWEEN NEUTROPHIL-LYMPHOCYTIC RATIO AND DIFFERENT COMORBIDITIES IN CORONAVIRUS-INFECTED PATIENTS - AGRAWAL, NIKHIL; BHARTI, AKASH; MITTAL, SHAAVI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Aim: The study’s aim was to determine the neutrophil-to-lymphocyte ratio (NLR) is most helpful predictor factor for COVID-19-related serious illness. Methods: A total of 51 patients with COVID-19 infection with laboratory-confirmed reports were enrolled in this study: Age, neutrophil-to-lymphocyte (LYMLYM) ratio (NLR), an examination, and comparison. Data analysis, compilation, and report writing were completed based on the acquired data. Using SPSS.ver-23, standard statistical procedures were used to analyze the mean and standard deviation, as well as the Pearson correlation. If p<0.05, it is deemed significant. Results: The mean hemoglobin level was 12.44±3.55%, the mean platelet count was 1.95±0.65 cumm, the mean white blood cell count was 17400 ±6455.22 cumm, and the mean NLR was 5.72±1.24. When we looked at people who had hypertension, diabetes mellitus, and high cholesterol, we found that the NLR value was significantly higher in people with these diseases (p=0.05). Conclusion: We found that NLR is an excellent way to predict COVID-19-infected patients who are likely to get a lot of other illnesses and have a lot of problems early on.